New Impression of Hotel in Sustainable Building Conversion and Adaptation Through University Campus - Mohammad Affendy, Omardin; Norzamzila, Mustafa; Khalimi Johan, Abd Hamid; Wan Dagang, Wan Ali (Penerbit UMP, 2011)
The feel and quality of the community within new features is strongly influenced by the character of the spaces between the buildings. The purpose of this paper is to highlight the feasibility studies of the new impression of hotel in Sustainable Building Conversion and Adaptation through University campus. The studies are done based on the results obtained from the community. The added of new facilities to the campus community will introduce the importance of hotel and it benefits to the campus. The Universiti Malaysia Pahang (UMP) hotel building need to be developed in order to solve the future problem such as the added value to the internal community by providing the internal training centre, other continuing development courses related to the UMP’s staffs. The new facilities will help to highlight new features due to the benefits of the community.